Effect of Combination Songga-Wood-Stem (Strychnos ligustrina Blume) and Antimalaria-ACT on IL-10 Production of Malaria - Kis - Djamiatun; Rahmi - Wirman; Noor - Wijayahadi (Faculty of Medicine, Universitas Diponegoro, 2022)
Malaria is one of the deadliest infectious diseases in the world. Artemisinin-Based-Combination-Therapy (ACT) an antimalaria recommended by WHO, is starting to experience resistance in Asia. Meanwhile the natural-product-immunoprotective and antimalaria-effect may benefice for malaria. Objective of this study was to determine the effect of combination of ethanolic-extract from Songga-wood-stem (EESWS) and ACT on IL-10, a protective-cytokine against malaria-immunopathology. This experimental-study used post-test-only-randomized-controlled-group-design. The thirty-Swiss-webster-mice were grouped into 5 groups. The one-group of healthy-mice (K1), and the four-groups infected with Plasmodium berghei ANKA (PbA) which were untreated-K2-group, ACT-treated-K3-group, EESWS-treated-P1-group, and EESWS-ACT-combination-treated-P2-group. IL-10-level of stimulated-splenocytes-culture was examined by ELISA-method. Data-analysis-used was One-Way-Anova-Welch-test and Post-hoc Games-Howell. P1 and P2-groups had higher IL-10-levels than K1 (p=0.038). Groups of P1 and P2 showed lower IL-10-levels than K3 (p=0.001). IL-10-level of P2-group was not different than P1 (p=0.135). The conclusion is the EEWS or EESWS-ACT-combination-therapy restrains the increase-splenic-IL-10-production above normal value in the healing phase of malaria infection.